Application of Moodle as Authentic Assessment in Learning Mathematics in SMK - HE, Chrisnawati; Wulandari, Arum Nur; Sutopo, Sutopo; Kuswardi, Yemi (Journal of Mathematics and Mathematics Education, 2020)
The purpose of this study was to develop an assessment system using Moodle e-learning to improve mathematics learning outcomes in terms of knowledge, skills and attitudes of students. The development design in this study is more on how to develop learning activities with authentic assessment that must be carried out by the teacher which of course will be very difficult if everything is paper-based. The implementation of a reliable assessment with easy administration by the teacher becomes the consideration of the researcher. And with regard to the pandemic conditions that are being experienced by the Indonesian nation, online learning is an option for students and teachers. Even in the assessment that must be carried out. For this reason, the Moodle application is an alternative that allows students to access teaching materials and practice problem solving easily. This is very interesting to do a development study in SMK, why? Because vocational students usually lack positive attitudes towards mathematics. The use of the Moodle application in learning mathematics in the classroom is certainly the teacher's job to limit the time to face students, and the lack of positive attitudes of these students into "energy" to optimize student abilities. This research was conducted at SMK Warga Surakarta, in class XII Machines, using the Thiagarajan RnD 4D steps, namely Define, Design, Develop and Disseminate. From this research, an authentic assessment instrument has been developed using the Moodle application on the Limit Function material. By reviewing the basic competencies in the Function Limit material, 20 questions were developed in the C2 (8 points), C3 (6 points) and C4 (6 points) categories and validated with a professional judgment on the test instrument. In the student attendance data, it appears that the desire of students to improve their understanding of the Limit Function material is quite high, more than 70% of students want to repeat the class independently. Also, the average student attendance was 13.4 out of 10 meetings planned in the teacher's lesson plan (1 meeting for the implementation of daily tests). From the average value of assignments, there was an increase in the grades in assignment 1 and assignment 2, but in assignment 3, the average score of student achievement decreased, this was possible because the material in assignment 3 was a continuation of the material for assignments 1 and 2, but if viewed from the frequency of doing assignments in each task session, there was a decrease in the number of frequencies. This can be seen in assignment 2, where the average student did the assignment 2.87 on task 1, and in task 2 the average student did 2.43 times with the results significantly increasing. Meanwhile, the average daily test for students in class XII M1 was 78.7, which means that the class average was above the school's KKM and 73.3% of students obtained learning outcomes above the KKM on the Function Limit material. It can be said that learning can improve student learning outcomes and motivate students, because from the response questionnaire, 86.7% of students said they were motivated to try the test to get good results.